Primary care practice-based care management for chronically ill patients (PraCMan) in German healthcare: outcome of a propensity-score matched cohort study - Senft, Jonas; Freund, Tobias; Wensing, Michel; Schwill, Simon; Poß-Doering, Regina; Szecsenyi, Joachim; Laux, Gunter (European journal of general practice, 2021)
Background Growing prevalence of chronic diseases is a rising challenge for healthcare systems. The Primary Care Practice-Based Care Management (PraCMan) programme is a comprehensive disease management intervention in primary care in Germany aiming to improve medical care and to reduce potentially avoidable hospitalisations for chronically ill patients.Objectives This study aimed to assess the effect of PraCMan on hospitalisation rate and related costs.Methods A retrospective propensity-score matched cohort study was performed. Reimbursement data related to patients treated in general practices between 1st July 2013 and 31st December 2017 were supplied by a statutory health insurance company (AOK Baden-Wuerttemberg, Germany) to compare hospitalisation rate and direct healthcare costs between patients participating in the PraCMan intervention and propensity-score matched controls following usual care. Outcomes were determined for the one-year-periods before and 12 months after beginning of participation in the intervention.Results In total, 6148 patients participated in the PraCMan intervention during the observation period and were compared to a propensity-score matched control group of 6148 patients from a pool of 63,446 eligible patients. In the one-year period after the intervention, the per-patient hospitalisation rate was 8.3% lower in the intervention group compared to control (p = 0.0004). Per-patient hospitalisation costs were 9.4% lower in favour of the intervention group (p = 0.0002).Conclusion This study showed that the PraCMan intervention may be associated with a lower rate of hospital admissions and hospitalisation costs than usual care. Further studies may assess long-term effects of PraCMan and its efficacy in preventing known complications of chronic diseases.